Beaver Ponds: Resurgent Nitrogen Sinks for Rural Watersheds in the Northeastern United States. Issue 5 (1st September 2015) - Lazar, Julia G.; Addy, Kelly; Gold, Arthur J.; Groffman, Peter M.; McKinney, Richard A.; Kellogg, Dorothy Q.
Abstract : Beaver‐created ponds and dams, on the rise in the northeastern United States, reshape headwater stream networks from extensive, free‐flowing reaches to complexes of ponds, wetlands, and connecting streams. We examined seasonal and annual rates of nitrate transformations in three beaver ponds in Rhode Island under enriched nitrate‐nitrogen (N) conditions through the use of 15 N mass balance techniques on soil core mesocosm incubations. We recovered approximately 93% of the nitrate N from our mesocosm incubations. Of the added nitrate N, 22 to 39% was transformed during the course of the incubation. Denitrification had the highest rates of transformation (97–236 mg N m −2 d −1 ), followed by assimilation into the organic soil N pool (41–93 mg N m −2 d −1 ) and ammonium generation (11–14 mg N m −2 d −1 ). Our denitrification rates exceeded those in several studies of freshwater ponds and wetlands; however, rates in those ecosystems may have been limited by low concentrations of nitrate. Assuming a density of 0.7 beaver ponds km −2 of catchment area, we estimated that in nitrate‐enriched watersheds, beaver pond denitrification can remove approximately 50 to 450 kg nitrate N km −2 catchment area. In rural watersheds of southern New England with high N loading (i.e., 1000 kg km −2 ), denitrification from beaver ponds may remove 5 to 45% of watershed nitrate N loading. Beaver ponds represent a relatively new and substantial sink for watershed N if current beaver populations persist. Core Ideas: In rural watersheds of southern New England with high N loading, denitrification from beaver ponds may remove 5–45% of watershed nitrate‐N loading. Beaver ponds represent a relatively new, substantial sink for watershed N if current beaver populations persist. Denitrification had the highest rates of nitrate transformation in our beaver pond study, with N2 as the dominant product.